2021
DOI: 10.2147/ijgm.s311959
|View full text |Cite
|
Sign up to set email alerts
|

PROZ May Serve as a Prognostic Biomarker for Early Hepatocellular Carcinoma

Abstract: Objective The occurrence and development of hepatocellular carcinoma (HCC) remain unclear. This study aimed to investigate potential diagnostic or prognostic markers for early HCC by applying bioinformatic analysis. Methods The gene expression profiles of early HCC and normal tissues from a TCGA dataset were used to identify differentially expressed genes (DEGs) and then analysed by weighted gene coexpression network analysis. The integrated genes were selected to const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…KEGG enrichment analysis of NT5E coexpressed genes showed a correlation with focal adhesion, suggesting that NT5E may be involved in the formation of drug resistance in HNSCC, which provides a reference for future treatment studies. Similarly, overactivation of the PI3K-Akt pathway is also an important mechanism of tumour growth and invasion, which shows the role of NT5E in tumour progression and suggests that NT5E is a potential target [ 32 34 ]. In general, NT5E is associated with immunosuppression of tumours [ 5 ], but we used TIMER analysis to show that NT5E is more strongly related to infiltration of many immune cells in HPV-negative HNSCCs, which have a poorer prognosis compared with HPV-positive HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG enrichment analysis of NT5E coexpressed genes showed a correlation with focal adhesion, suggesting that NT5E may be involved in the formation of drug resistance in HNSCC, which provides a reference for future treatment studies. Similarly, overactivation of the PI3K-Akt pathway is also an important mechanism of tumour growth and invasion, which shows the role of NT5E in tumour progression and suggests that NT5E is a potential target [ 32 34 ]. In general, NT5E is associated with immunosuppression of tumours [ 5 ], but we used TIMER analysis to show that NT5E is more strongly related to infiltration of many immune cells in HPV-negative HNSCCs, which have a poorer prognosis compared with HPV-positive HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…PROZ’s relationship with tumors: Recent research has shown that PROZ can be used as a marker of pancreatic cancer through protein identification in the serum [ 13 ]. At the same time, some studies in HCC have shown through a public database analysis that PROZ is a marker of early-stage HCC, and that a low expression of PROZ is associated with poor prognosis of HCC [ 14 ]. Coincidentally, another database-dependent analysis showed that PROZ is also one of the gene markers associated with the prognosis of HCC [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our data demonstrate a stronger discriminatory effect of DE IGPs over DE proteins, indicating the potential of N-glycosylation as a diagnostic biomarker for HCC. Previous stud-ies have reported the usefulness of various protein candidates, such as VCAM1, B2M, and PROZ, in the diagnosis of HCC and other diseases[26][27][28]. For instance, elevated levels of VCAM1 in the plasma have been observed in patients with HCC, colorectal cancer, and gastric cancer, suggesting its involvement in angiogenesis and the pathogenesis of HCC[29].…”
mentioning
confidence: 99%